2016
DOI: 10.1177/0957650916671026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on slot-type casing treatment injection flow in an axial transonic compressor

Abstract: The purpose of this work is to understand the properties of the injection flow through slots opening surfaces with steady and unsteady simulations. The feasibility of evaluating slot effectiveness by steady results is demonstrated. Transient features of injection flow are detailed investigated. Numerical investigations are carried out in a 1.5 axial transonic compressor stage at a specified rotating speed with seven kinds of slot-type casing treatments. Comparisons between steady/unsteady results show that dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Zhu et al [174] distinguished a linear correlation between the injection mass flow rate and stall margin improvement from numerical results.…”
Section: Injection Suction and Recirculationmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhu et al [174] distinguished a linear correlation between the injection mass flow rate and stall margin improvement from numerical results.…”
Section: Injection Suction and Recirculationmentioning
confidence: 99%
“…Recently, the investigations have shown that, with the proper selection of casing treatment parameters, both the stall margin and the performance can be improved [170]. The most important design parameters for a self-circulating casing treatment are the width and position of the bleed slot [171][172][173], recirculation flow rate [172] and casing porosity [174].…”
Section: Injection Suction and Recirculationmentioning
confidence: 99%
See 1 more Smart Citation